2018
DOI: 10.1186/s12955-018-0906-y
|View full text |Cite
|
Sign up to set email alerts
|

Health and quality of life outcomes impairment of quality of life in type 2 diabetes mellitus: a cross-sectional study

Abstract: BackgroundType 2 diabetes mellitus (DM2) is a chronic disease, and for treatment to succeed, it is necessary to harmonize the mental health of the patient with the environment, which impacts quality of life and adherence to medical regimens. The objetive of this study is describe the quality of life of patients with DM2 and the factors relates to its modification.MethodsThis investigation was a cross-sectional study. Patients over 18 years of age with DM2 were selected. The following variables related to quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
53
0
22

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 42 publications
11
53
0
22
Order By: Relevance
“…Besides, as Projection involves the justification of aggression against external sources of frustration, such a defense mechanism might lead to the justifying of covert hostile and counter dependent behaviors, such as a bad lifestyle and reduced treatment adherence, in turn negatively affecting one's physical status. This is in line with previous findings regarding the high levels of frustration and anger in patients with T2DM, mainly due to restrictions on food and comorbidities in sexual life (Zurita-Cruz et al, 2018;Al Anazi et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Besides, as Projection involves the justification of aggression against external sources of frustration, such a defense mechanism might lead to the justifying of covert hostile and counter dependent behaviors, such as a bad lifestyle and reduced treatment adherence, in turn negatively affecting one's physical status. This is in line with previous findings regarding the high levels of frustration and anger in patients with T2DM, mainly due to restrictions on food and comorbidities in sexual life (Zurita-Cruz et al, 2018;Al Anazi et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…[8][9][10] Different studies reported that DM has a negative impact on the overall QoL of DM patients. [11][12][13][14] Nevertheless, as these studies, different tools were used among different populations; hence, it is still debatable to know the correct findings of the QoL of DM patients in different cohorts of patients in different countries. [11][12][13][14] There are two main types of research tools which usually use to measure QoL among DM patients, that is, generic or disease-specific.…”
Section: Original Articlementioning
confidence: 99%
“…For example, the SF-36 covers some aspects of symptoms, functioning, and general health perceptions. At the same time the SF-36, and its many variants, are frequently referred to as measures of quality-of-life (QoL), which they clearly are not [3][4][5] . If researchers are unclear about what a PROM is intended to measure, the construct definition of the instrument is inadequate.…”
Section: C00; I10mentioning
confidence: 99%